Persistence of right ventricular dysfunction and altered morphometry in asymptomatic preterm Infants through one year of age: Cardiac phenotype of prematurity. (9th July 2019) - Erickson, Collin T.; Patel, Meghna D.; Choudhry, Swati; Bisselou, Karl Stessy; Sekarski, Tim; Craft, Mary; Li, Ling; Khuffash, Afif El; Hamvas, Aaron; Kutty, Shelby; Singh, Gautam K.; Levy, Philip T.
Abstract: Introduction: Prematurity impacts myocardial development and may determine long-term outcomes. The objective of this study was to test the hypothesis that preterm neonates develop right ventricle dysfunction and adaptive remodelling by 32 weeks post-menstrual age that persists through 1 year corrected age. Materials and Methods: A subset of 80 preterm infants (born <29 weeks) was selected retrospectively from a prospectively enrolled cohort and measures of right ventricle systolic function and morphology by two-dimensional echocardiography were assessed at 32 weeks post-menstrual age and at 1 year of corrected age. Comparisons were made to 50 term infants at 1 month and 1 year of age. Sub-analyses were performed in preterm-born infants with bronchopulmonary dysplasia and/or pulmonary hypertension. Result: In both term and preterm infants, right ventricle function and morphology increased over the first year (p < 0.01). The magnitudes of right ventricle function measures were lower in preterm-born infants at each time period (p < 0.01 for all) and right ventricle morphology indices were wider in all preterm infants by 1 year corrected age, irrespective of lung disease. Measures of a) right ventricle function were further decreased and b) morphology increased through 1 year in preterm infants with bronchopulmonary dysplasia and/or pulmonary hypertension (p < 0.01). Conclusion: Preterm infants exhibit abnormal right ventricle performance with remodelling at 32 weeks post-menstrual age that persists through 1 year corrected age, suggesting a less developed intrinsic myocardial function response following preterm birth. The development of bronchopulmonary dysplasia and pulmonary hypertension leave a further negative impact on right ventricle mechanics over the first year of age.